Influence of seat pitch and body anthropometry parameters on aircraft passengers' seating comfort - Ahmad Habibillah, Nadia Hanani; Ismail, Nur Hidayah; Romli, Fairuz Izzudin (The Aeronautical and Astronautical Society of the Republic of China, 2022)
In-flight seating comfort has been an important decision factor for many air transport passengers in choosing the offered flight services. The provision of good seating comfort increases the possibility of returning passengers and their loyalty towards the airlines. In general, the in-flight seating comfort can be affected by various factors including seat pitch and anthropometry of the passengers. To study the influences of these parameters, a sitting experiment is done in aircraft cabin mock-up. 30 volunteers of different anthropometric dimensions have participated in this study and the seat pitch setting is varied at six different values between 26 inches (66.04 cm) to 41 inches (104.14 cm). Based on ANOVA results of comfort assessment ratings given by participants, seat pitch is shown to be the most influential factor for seating comfort with 94.02% contribution to its rating. In the meantime, five top influential sitting posture anthropometric measurements are forward grip reach, elbow height, buttock knee length, crown buttock height and shoulder height, which have a cumulative 5.03% contribution to the variability in the seating comfort rating. A regression model to capture the underlying relationship between the seating comfort and these influential factors has been constructed.